Potensi Desa Kanoman melalui Hasil Pertanian dan Hasil Perkebunan - Sasmita, Raymundo Patria Hayu (Jurnal Atma Inovasia, 2021)
Kanoman Village is located in Panjatan District, Kulon Progo. The people of Kanoman Village have the majority of their livelihoods as farmers. This village grows a lot of rice, chilies, onions and there are also many coconut plantations. A lot of rice farming produces straw which can be reused for animal feed. Apart from Jermi, this village has many coconut plantations, coconut husk damana can be used as a handsanitizer. The purpose of conducting KKN in this village is to provide skills to the community to cultivate the existing village potential. The method to be carried out is making the straw fermentation and extracting coconut husk simply. The results of this KKN are expected to be of benefit to the community in Kanoman Village